POTENSIAL STUDY OF WASTE MANNAGEMENT EXTRACURRICULAR TO DEVELOP STUDENTSâ ENVIRONMENTAL CARING CHARACTER IN SMAN 13 SEMARANG - Prabawati, Desi Ayu; Tri Martuti, Nana Kariada; Isnaeni, Wiwi (Journal of Biology Education, 2018)
SMAN 13 Semarang is one of the schools in Semarang that develops waste management as an extracurricular activities. However, students at SMA N 13 Semarang are still seen littering, using plastic as food wrappers, and have not sorted out garbage. Students are expected to have high awareness to contribute to reducing environmental damage by participating in waste management. This study aims to examine the extracurricular potential of waste management in developing the environmental caring character of the students. This research uses qualitative approach with case study research type. The number of primary informants is 15 students who are active in extracurricular waste management. The results showed that students have basic knowledge about the environment through the subject of PLH but have not been able to develop it. Curiosity has been formed because students have an interest in watching television shows and reading environmental related articles, but in terms of providing information media is still limited through teachers. Students throw garbage at the place provided, but to sorting garbage still less. Based on the results of research and discussion can be concluded that the characters that have been formed is used to maintain the cleanliness of the environment, used to dispose of waste in place, the school provides cleaning equipment, and responsible for maintaining environmental cleanliness. Character that has been formed and still requires teacher assistance is the character to sort out garbage, provide communication media and explore knowledge about the environment.